Optimalisasi Produktivitas dan Efisiensi Kewirausahaan Melalui Pengembangan Keterampilan Manajerial - Dida Maulidya Al Afshana; Agung Winarno; Wening Patmi Rahayu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research is motivated by the importance of managerial skills in improving business productivity and efficiency, particularly in the entrepreneurial sector, which faces the challenges of competition, market changes, and limited resources. The objective of this study is to analyze the role of managerial skills development and its contribution to optimizing entrepreneurial performance. The method used is a Systematic Literature Review (SLR), which examines various relevant scientific publications and then categorizes the findings to obtain a comprehensive overview of effective strategies for improving managerial competency. The results indicate that technical skills, human relations skills, and conceptual skills play a significant role in supporting decision-making processes, resource management, and adapting business strategies to business dynamics. The findings also indicate that training, mentoring, continuous learning, and the use of technology are development strategies capable of significantly increasing productivity and efficiency. The implications of this research emphasize that improving managerial skills is a strategic necessity for entrepreneurs to strengthen competitiveness, increase operational effectiveness, and promote business sustainability. Furthermore, this research provides a basis for the development of more structured training programs and supporting policies to strengthen the managerial capacity of entrepreneurs.